FBM engagement session & tours to branch campuses - UiTM, Faculty of Business and Management (UiTM, 2023)
An engagement session was held with Professor Dr. Firdaus Abdullah, Dean of the Faculty of Business Management (FBM), and his delegation to articulate the strategic direction and initiatives of the faculty, holistically underscoring the objective of fortifying the Faculty of Business and Management. In this engagement session, Professor Dr. Firdaus Abdullah delineated the strategic trajectory of FBM, emphasizing its commitment to augmenting UiTM's standing and subject ranking in the QS World University Rankings, thereby garnering acknowledgement from esteemed professional and industry bodies. Additionally, the faculty announced its commitment to facilitating the pursuit of Ph.D qualifications among lecturers at UiTM branches, propelling their progression to elevated academic positions.